Myeloarchitecture, intra- and interhemispheric and thalamocortical connections of area 3b representing the teeth and tongue in galagos - Hui-Xin Qi; Barbara M. J. O’Brien; Jamie L. Reed; Jon H. Kaas (Proceedings of the National Academy of Sciences, 2026)
The representations of the face and oral cavity occupy a large but understudied portion of primary somatosensory cortex (S1 or area 3b) in primates. These studies are clearly important in processing food, taste, and vocalizations. Little is known about the neuronal representations of the teeth and tongue, their relationship with myeloarchitecture, and their cortical and thalamic connections in area 3b of strepsirrhine galagos. In owl and squirrel monkeys, and likely in macaque monkeys, the most lateral portion of S1 represents the face, teeth, and tongue in a series of myelin-dense ovals, including ovals for the contralateral teeth and tongue and ipsilateral teeth and tongue. As this complex representation of the teeth and tongue may differ among mammals and even primates, we sought to evaluate these representations in the galagos, representing an early branch of primates. Using a combination of neuronal responses to touch, neuroanatomical tracer injections, and tissue processing to reveal anatomical area borders, we found that lateral S1 in galagos resembles those of studied monkeys by having a series of ovals that double the representation of the tongue and teeth, along with similar intracortical, callosal, and thalamic connections, suggesting that these features of S1 emerged in the first primates.